The Effect of Critical Thingking to Improve Student’s Reading Skill at SMA Negeri 1 Sanana - Umasugi, Faujia; Saban, Amrin Hi.; Aufat, Susanti (International Journal of Education, Information Technology, and Others, 2025)
The aim of this research was to determine whether or not there was an effect of critical thinking on the reading skills of second grade students at SMA Negeri 1 Sanana. Research used quantitative research methods using a non-equivalentcontrol group research design. The samples in this study were natural science 1 and social science 1 with a sample size of 15 students and were selected using stratified random sampling. This research was conducted using two groups, namely the experimental group and the control group. Both groups were then given a pre-test and post-test. However, only the experimental group received treatment. This research instrument is multiple choice and consists of 20 questions. In analyzing the data, research used SPSS-22 to analyze descriptive data to determine students' categories and grades and inferential analysis to determine normality, homogeneity, reability and hypothesis tests (independent sample test). The results of data analysis show that there is a difference between students' scores on the pre-test and post-test, the results of the effect of effective critical thinking, proven by the students' results before and after being given treatment, their score with the average pre-test score for experimental class students is 55 .00 while the average post-test score was 78.80 after treatment, and also the control group had a pre-test total score of 62.33, and the students' post-test total score was 68.53. in the inferential analysis the data from the pre-test and post-test were normal and homogeneous, is so the researcher used the t-test by comparing the results of the two groups then the independent test results of the samples in the experimental class were 3,740> 1.76 with a 2-tailed sig value of 001 <0.05 and in the control class it is -1.568>.1.76 with a tailed sig-2 value of 128.>0.05. This means that the effect of critical thinking to improve students' reading skills in the experimental class has a significant influence. Researcher concluded that the critical thinking can give good effects to improved the reading skills of second grade students at SMA Negeri 1 Sanana because it allows students to conclude and understand reading material, there for the researcher recommend to English teachers in order to apply critical thinking to students to provide understanding and improve student’s reading skill.